Mengembangkan Keterampilan Memahami Cerita, Menulis, dan Kosakata Bahasa Inggris Anak TK B melalui Kegiatan Membacakan Buku Cerita [Developing Comprehension, Writing, and Vocabulary Skill of Kindergarten 3 Students Through Story Reading Activity] - Lely Puspitasari (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2022)
Literacy skill is essential for students’ academic success. Yet, language learning at schools takes less attention in comprehension skill and vocabulary that are integral parts of reading and writing as it focuses more on reading words. This research investigated the implication of story reading activities on the development of Kindergarten 3 students’ comprehension, writing, and vocabulary skill. It particularly aimed to: (1) describe students’ comprehension, writing, and vocabulary skill before the implementation; (2) describe the implementation of story reading activity; (3) analyze the development of students’ comprehension, writing, and vocabulary; (4) identify the obstacles during the implementation process. The classroom action research conducted in this study was carried out in three cycles. The research subjects were 20 students. Data were collected by using observation, field notes, interview, and written test, then analyzed with descriptive qualitative. The results showed: (1) the students still needed time to develop the three target skills; (2) the implementation used reading strategies consistently; (3) there is significant improvement with N-gain of 0.8 for comprehension skill, 0.63 for writing skill, and 0.8 for vocabulary knowledge; (4) suitable test formation made to ease students in doing the test, personal approach was applied to deal with certain students’ characteristic, and adjustment to learning schedule was made in conducting this research.